Implementation of reading tasks in efl classroom: a study of teacher, students and text relations - Trevisani, Ana Paula (2004)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/inglês e Literatura Correspondente